The Effect of Brain Drain on Indonesia's Economic Competitiveness: A Case Study of the Phenomenon #KaburAjaDulu - Yosefin; Chen, Katty (Indonesian Journal of Entrepreneurship and Startups, 2025)
The brain drain phenomenon is increasingly in the spotlight, a condition in which skilled Indonesian workers choose to work abroad, especially after the viral #KaburAjaDulu social campaign. This research aims to understand how this migration trend affects Indonesia's economic competitiveness, particularly in terms of talent loss, productivity and national innovation capacity. Using a descriptive qualitative approach and a secondary case study, this research drew on data from official government reports, scientific publications, and media articles. The results show that if not managed seriously, brain drain can hamper long-term economic growth. Therefore, more inclusive and visionary policies are needed to retain domestic talent and strengthen the work ecosystem that supports the younger generation to stay in Indonesia